2019
DOI: 10.1175/jcli-d-18-0437.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the MJO under Greenhouse Gas–Induced Warming in CMIP5 Models

Abstract: This study investigates changes to the Madden–Julian oscillation (MJO) in response to greenhouse gas–induced warming during the twenty-first century. Changes in the MJO’s amplitude, phase speed, and zonal scale are examined in five models from phase 5 of the Coupled Model Intercomparison Project (CMIP5) that demonstrate superior MJO characteristics. Under warming, the CMIP5 models exhibit a robust increase in the spectral power of planetary-scale, intraseasonal, eastward-propagating (MJO) precipitation anomali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 81 publications
5
47
0
Order By: Relevance
“…To provide confidence in future MJO projections, we use a subset of CMIP5 models that have been assessed to produce good MJO variability in current climate. Hence, we consider here the superset of CMIP5 models that were assessed in Bui and Maloney (, ) and Rushley et al () to produce good MJO variability in current climate. These include BCC‐CSM1‐1, CMCC‐CMS, CMCC‐CM, CNRM‐CM5, GFDL‐CM3, IPSL‐CM5B‐LR, MIROC5 (with three ensemble members), MRI‐CGCM3, and NorESM1‐M.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide confidence in future MJO projections, we use a subset of CMIP5 models that have been assessed to produce good MJO variability in current climate. Hence, we consider here the superset of CMIP5 models that were assessed in Bui and Maloney (, ) and Rushley et al () to produce good MJO variability in current climate. These include BCC‐CSM1‐1, CMCC‐CMS, CMCC‐CM, CNRM‐CM5, GFDL‐CM3, IPSL‐CM5B‐LR, MIROC5 (with three ensemble members), MRI‐CGCM3, and NorESM1‐M.…”
Section: Methodsmentioning
confidence: 99%
“…To address the first challenge, models can be prefiltered to select only those that produce a good MJO before doing projections. Hence, in the current study, we will analyze 11 CMIP5 simulations of the 21st century from models that have been assessed by Bui and Maloney (, ) and Rushley et al () to have a good MJO.…”
Section: Introductionmentioning
confidence: 99%
“…Arnold et al 23 noticed that intraseasonal OLR variance increased with the increase in tropical SST from his aquaplanet experiment using the NCAR community Atmospheric model. Rushley et al 24 examined the projected changes of MJO in response to greenhouse-gas induced warming during the twenty-first century using five CMIP5 models. They observed that the MJO related precipitation variation is likely to be stronger in future warmer climates.…”
Section: Introductionmentioning
confidence: 99%
“…Climatological monthly precipitation shows different features of number and phase of the peak among the stations such as local peaks in August and November at Chico, in June and October at Rio Piedras, Chamon in November, and Esperanza; these differences in phases may be due to local-scale complex orographic convection activities induced in the ITCZ migration and intraseasonal oscillations that module the convective activity in the tropics as MJO [27].…”
Section: Methods and Datamentioning
confidence: 99%
“…Seasonal changes of partitioning of net radiation at the Earth’s surface to sensible and latent heats affects the diurnal variation of precipitation through atmospheric stability [25]. On interannual time scale, El Niño–Southern Oscillation (ENSO) [16, 26] and Madden-Julian Oscillation (MJO) affect the diurnal variation by changing the amplitude but not the phase [16, 27]. The upper Río Chagres basin is a sub-basin on the eastern side of the Panama Canal watershed (Fig 1).…”
Section: Introductionmentioning
confidence: 99%